Keanekaragaman Ikan Hasil Tangkapan Nelayan di Pelabuhan Pulau Baai Kota Bengkulu - Naftalia Artaria Hutabarat; Indra Sakti; Sutarno Sutarno; Aprina Defianti; Ariefa Primairyani; Euis Nursa'adah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Pulau Baai Port is a crucial resource used as the main sea transportation route for some commodities and goods needed by principals when traveling to or from Bengkulu. Data collection was carried out at three stations The method used to determine stations is purposive sampling. Water quality data collection was also carried out at the three stations. The fish identification method is carried out by looking at morphological characteristics to facilitate classification using the Marine Fishes of the south identification book. A total of 18 species of fish found in the waters of the City of Bengkulu landed at the port Pulau Baai namely white pomfret fish (Pampus argenteus), black pomfret fish (Parastromateus niger), mackerel fish (Scomberomorini), mujair fish (Oreochromis mossambicus), beledang fish (Trichiurus lepturus), next fish (Pleuronectiformes), manyung fish (Arius thalassinus ), kerong kerong fish (Terapon jarbua), sea cork fish (Channa striata), big eye tuba fish (Thunnus obesus), mullet fish (Moolgarda seheli), anchovies (Engraulidae), mackerel fish (Scomberomorini), beleberan fish (Opisthopterus tardoore), Cladi fish (Osphronemus goramy), Kape-kape fish (Pentaprion longimanus), Gulamo fish (Johnius trachycephalus), and Sengin fish (Eleutheronema tetradactylumThen, from the results of calculating the diversity index at these three stations, the values range from 2.46-2.07, (medium). It can be concluded that the results of the ecological analysis at the three stations have moderate diversity with a uniform composition and no species dominates.